False cognates: a minefield for Algerian non-professional translators (Philologia, 2021)
The aim of this paper is to set out a major obstacle, false cognates, faced by many Algerian students wishing to translate from and into French and English.
Keywords: false cognates; faux amis; grammatical/lexical false friends; totally/partially deceptive cognates